2004
DOI: 10.1111/j.1600-0501.2004.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

The immediate rehabilitation by means of a ready‐made final fixed prosthesis in the edentulous mandible: a 1‐year follow‐up study on 50 consecutive patients

Abstract: Although a two-stage procedure with symphyseal oral implants can lead to a long-term (15 years) 99% cumulative survival rate, a one-stage approach with immediate loading via prefabricated elements seems to offer a short-term acceptable outcome with significantly lower costs. A series of 50 consecutive patients, not eliminated for any systemic or smoking condition, received at the department of periodontology three implants in the symphyseal area, connected by a very rigid horse shoe-shaped titanium bar. A fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 15 publications
7
65
0
8
Order By: Relevance
“…124 Furthermore, sensitivity analysis suggests that smoking significantly affects the survival of implants inserted only in the maxilla. The lack of statistical significance for the mandible is surprising but is most likely explained by the limited number of studies 16,24,28,34,35 reporting implant survival for smokers and non-smokers exclusively in the inferior jaw. A previous review 125 on the subject suggested that smoking may be a significant risk factor with an adverse effect on implant survival and success in areas of loose trabecular bone, but may not be as significant for good bone sites.…”
Section: Discussionmentioning
confidence: 86%
“…124 Furthermore, sensitivity analysis suggests that smoking significantly affects the survival of implants inserted only in the maxilla. The lack of statistical significance for the mandible is surprising but is most likely explained by the limited number of studies 16,24,28,34,35 reporting implant survival for smokers and non-smokers exclusively in the inferior jaw. A previous review 125 on the subject suggested that smoking may be a significant risk factor with an adverse effect on implant survival and success in areas of loose trabecular bone, but may not be as significant for good bone sites.…”
Section: Discussionmentioning
confidence: 86%
“…17 Implant splinting with a rigid framework in immediate load protocols was already recommended by different authors 7,8,18,19 to limit micromovement and minimize the risk of early implant failure; nevertheless, in their paper, Nikellis and colleagues consider the threshold of 32 Ncm for the implants inserted to be sufficient to use a provisional restoration without a rigid metal reinforcement. The success rate and the crestal bone remodeling were very similar between test and control groups without statistically significant differences, showing that even implants without good primary stability can achieve and maintain osteointegration with an immediate loading protocol when splinted to implants with good IT values.…”
Section: Discussionmentioning
confidence: 99%
“…The exposition to these mechanical stresses before biological integration may lead to the implant micromovements and finally to an early implant failure. [7][8][9] Degidi and colleagues recently published several papers to describe the intraoral welded bar technique that seems to offer a solution for the stabilization of the implants placed with low IT values. 4,5 As a consequence, modified drilling guidelines to undersize the preparation and new implant designs were introduced for the improvement of primary stability.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of IL has been actively investigated, mainly in situations of the edentulous mandible 22,24,27‐32 . In a human histologic study, immediately loaded implants in the edentulous mandible demonstrated high bone‐to‐implant contacts, ranging from 78% to 85% 29 .…”
mentioning
confidence: 99%